DoubleTransfer at MEDIQA 2019: Multi-Source Transfer Learning for Natural Language Understanding in the Medical Domain. - Xu, Yichong; Liu, Xiaodong; Li, Chunyuan; Poon, Hoifung; Gao, Jianfeng (BioNLP 2019, 2019)
This paper describes our competing system to enter the MEDIQA-2019 competition. We use a multi-source transfer learning approach to transfer the knowledge from MT-DNN (Liu et al., 2019b) and SciBERT (Beltagy et al., 2019) to natural language understanding tasks in the medical domain. For transfer learning fine-tuning, we use multi-task learning on NLI, RQE and QA tasks on general and medical domains to improve performance. The proposed methods are proved effective for natural language understanding in the medical domain, and we rank the first place on the QA task.